Odpowiedzi

Najlepsza Odpowiedź!
2010-03-05T08:20:03+01:00
A) 2(x-3) + 3(4-x) =5
2x-6+12-3x=5
-x+6=5
x=1

b)3(x-4) - 2(2x- 5) = -4
3x-12-4x+10=-4
-x-2=-4
x=2

c) 2(x+4) - 5(x+3) = 2
2x+8-5x-15=2
-3x-7=2
3x=-9
x=-3

d) -2(x+3) + 4 (2x+3) = -6
-2x-6+8x+12=-6
6x+6=-6
6x=-12
x=-2
2 3 2
2010-03-05T08:24:13+01:00
A)2x-6+12-3x=5
2x-3x=5+6-12
-x=-1/(-)
x=1
b)3x-12-4x-10=-4
3x-4x=-4+12+10
-x=18/(-)
x=-18
c)2x+8-5x-15=2
2x-5x=2-8+15
-3x=9/(-3)
x=-3
d)-2x-6+8x+12=-6
-2x+8x=-6+6-12
4x=-12/4
x=-3
1 5 1
2010-03-05T08:26:01+01:00
A)2(x-3) + 3(4-x) =5
2x-6+12-3x=5
-x=5-6
x=1

b)3(x-4) - 2(2x- 5) = -4
3x-12-4x+10=-4
-x=-4+2
-x=-2
x=2

c) 2(x+4) - 5(x+3) = 2
2x+8-5x-15=2
-3x=2+7
-3x=9 /:-3
x=-3

d) -2(x+3) + 4 (2x+3) = -6
-2x-6+8x+12=-6
6x=-6+6
6x=0
x=0

Równanie sprzeczne
1 1 1